Effect of Spraying Salicylic Acid and Potassium on Sweet Pepper Growth under Water Stress (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
This experiment was conducted during the spring growing season 2017 in private farm of Babylon to study the impact of spraying salicylic acid , potassium under water stress and their interaction in sweet pepper growth under water stress. Plants were sprayed three times in 20 days intervals with three levels of Salicylic acid(SA) (0 ,50 and 100 mg. L-1) , three levels potassium with ( 0, 1000 and 2000 mg. L-1) and three irrigation times (5 ,10 ,15 )days. Complete Randomized Design (C.R.D ) with three replicates. Means were compared by L.S.D.O.O5 . Plant high, leaves the number, living area, Auxin(IAA) and potassium content increased with the increase in SA, K concentrations, D1 and interaction between them. D3 significantly decreased vegetative growth and IAA, but increased proline, catalase, SOD and ABA. Also, most of the characters were significantly influenced by an interaction between D3, SA and K concentrations.